Impact of financial inclusion and banking characteristics on banking stability in Indonesia - Linda Rosalina; Diah Wahyuningsih (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
This study aims to examine the impact of financial inclusion and banking characteristics (bank size, Capital Adequacy Ratio (CAR), and Non-Performing Loans (NPL)) on the stability of the Indonesian banking sector from 2009 to 2019. The sample in this research comprises 22 banks in the BUKU 3 category and 7 banks in the BUKU 4 category. The data processing method employed is panel data analysis. The fixed effect model was selected as the most suitable model for this study. This research indicates that the financial inclusion variable significantly negatively impacts banking stability due to uneven access to financial inclusion and low financial literacy regarding banking products. Additionally, banking characteristics negatively influence banking stability through the NPL and bank size variables. In contrast, the CAR variable significantly positively affects the banking stability variable. Therefore, expanding financial access through financial education about utilizing and selecting financial service products that cater to the community's needs is essential. This will enhance the benefits of financial inclusion in society and subsequently positively affect banking stability in Indonesia.